A study on the factos that influence ASNB brand loyalty / Nik Nur Aswad Nik Sulaiman - Nik Sulaiman, Nik Nur Aswad (2011)
PNB through its wholly own subsidiary company, ASNB is already 32 years in unit trust industry. So, there issue arise here is to determine whether ASNB has brand loyalty or vice versa. This study focus four factors which are brand name, promotion, service quality and dividend. Whether these four factor contribute to enhance ASNB brand loyalty or vice versa. From this study, it is found that brand name, service quality and dividend controbute to brand loyalty of ASNB. It is found that ASNB has brand name, service quality and dividend since it already 32 years in unit trust industry. Promotion is key in marketing strategy, however, ASNB still lack of promotion due several reason since ASNB likely move secretly in order to avoid any issue arise since its effort to help Malay and Bumiputera in term of economic and financing. ASNB do a lot of promotion but sometimes public especially Malay and Bumiputera do not alert with its programs. So, it can be concluded that ASNB has its own brand loyalty. Future research is whether status halal is contribute or vice versa to brand loyalty